Injuries in female soccer athletes: risk of injury across different phases of the menstrual cycle - Santos, W. R.; Camarotti Júnior, F.; Barbosa, D.; Ginnari, K. V.; Gomes Dos Santos, A. K. S.; Timoteo, B. O.; Costa, M. C.; Fernandes da Costa, M. S.; Paes, P. P. (Research Quarterly for Exercise and Sport, 2025)
The Menstrual Cycle (MC) involves hormonal changes that impact physical performance and increase the risk of injuries in female athletes. This study aimed to evaluate the injury risk in female soccer players during different phases of the MC, along with their characteristics, aiming at prevention and training strategies. It is a cross-sectional, exploratory, and retrospective study with Brazilian professional female soccer players. The sample consisted of 53 athletes (mean age 21.7 ± 4.9 years), 20 (37.7%) of whom had injuries in the last season. All participants had a regular MC and were registered in the professional roster. Data were collected through face-to-face interviews, covering personal and sports information, injury history in the last 12 months, and gynecological conditions. Injuries were correlated with the phases of the MC. The statistical analysis used the Pearson x2 test to compare the occurrence of injuries between the MC phases, with significance set at p < .05. A significant association was found between injuries and the phases of the MC, with the early follicular phase showing the highest proportion of injury rates (35.0%; p < .001; OR = 37.20), especially among midfielders (42.8%). Of these, 66.7% sustained contact injuries, all during training, with joint origins localized in the knee. Thus, we suggest that the early follicular phase may represent a period of increased vulnerability to injury risk. However, prospective and longitudinal studies across various leagues are needed to clarify the influence of the MC on these athletes` injuries.